2004
DOI: 10.1021/jo035712x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gramicidin S and Its Analogues via an On-Resin Macrolactamization Assisted by a Predisposed Conformation of the Linear Precursors

Abstract: A simple and efficient preparation of gramicidin S and its analogues is described. It involves solid-phase peptide synthesis and on-resin macrolactamization without side chain protection, affording cyclic products in high yield and high purity. The high specificity of the cyclization reaction was shown to originate in the formation of a pre-organized conformation of the linear biosynthetic precursor of gramicidin S. This facile method will provide convenient access to the analogues of the natural product for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…Previously, Wadhwani and Bu investigated the pre-fold of the linear native gramicidin S decapeptide substrate [25,26]. They were able to show that even the linear substrate adopts a similar b sheet structure to gramicidin S itself.…”
Section: Chemistry and Biologymentioning
confidence: 99%
“…Previously, Wadhwani and Bu investigated the pre-fold of the linear native gramicidin S decapeptide substrate [25,26]. They were able to show that even the linear substrate adopts a similar b sheet structure to gramicidin S itself.…”
Section: Chemistry and Biologymentioning
confidence: 99%
“…化学基元组学研究的目的之 一就是用化学合成技术仿真自然界的生物合成规律, 以相对较低的成本、快速地合成大量的类天然产物, 为药物筛选提供可持续发展的物质资源. 然而, 通过厘清它的合成机理, 化学家采用简单 的 1-乙酰氨基, 2-巯基乙烷代替肽携带蛋白, 用氨水 做催化剂即可高效率地合成 [26] . 实际上, 没有绝对单靶标作用的药物, 只有尚未 知晓更多作用靶标的药物.…”
Section: 化学基元组装的基本规律unclassified
“…Alanine scanning of the cyclic peptide showed that the Pro-2 residue is crucial for maintaining the -sheet structure while Pro-7 is substitutable [8] while more recent reports show ring sizes less than 10 amino acid residues still showed some moderate antibacterial activity [9]. GS interacts with lipid membranes and expresses its antibacterial activity via interaction with membrane phospholipids, disrupting the permeability barrier of the outer Gram negative membrane, allowing molecular translocation, while the inner cytoplasmic membrane shows increased potassium (K+) efflux [10].…”
Section: Gramicidinsmentioning
confidence: 99%